2022
DOI: 10.1088/1361-648x/ac8b4f
|View full text |Cite
|
Sign up to set email alerts
|

Structural evolution and relative stability of vanadium-doped boron clusters

Abstract: Cluster is the intermediate of individual atom and larger agglomeration. The structural evolutions of clusters are critically important to explore the physical properties of bulk solids. Here, we carry out systematic structure predictions of medium-sized vanadium-doped boron clusters by using CALYPSO method combined with DFT calculations. A great deal of low-lying isomers with attractive geometries are discovered, such as the crown-like VB18 − cluster and the drum-like VB20 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 57 publications
0
6
0
Order By: Relevance
“…[ 98 ] By CALYPSO, stable structures of transition metal (including Mo, W, Ta, Rh, Co, Ru, Zr, Sc, Ir, Nb, Cr, V, Mn, Fe, Ni, Pd, Ti, Hf) doped B clusters were widely studied. [ 99–120 ] Interestingly, transition metal doping can convert the ground‐state structure of small‐sized boron cluster, B 24 , from a quasi‐planar structure to a cage structure (Figure 18b). [ 99 ] Alkaline metal doping of boron clusters has also been extensively studied by CALYPSO code, which suggests that alkaline metal doping can greatly improve the stability of boron clusters (Figure 18c).…”
Section: Introduction To Existing Cluster Search Methodsmentioning
confidence: 99%
“…[ 98 ] By CALYPSO, stable structures of transition metal (including Mo, W, Ta, Rh, Co, Ru, Zr, Sc, Ir, Nb, Cr, V, Mn, Fe, Ni, Pd, Ti, Hf) doped B clusters were widely studied. [ 99–120 ] Interestingly, transition metal doping can convert the ground‐state structure of small‐sized boron cluster, B 24 , from a quasi‐planar structure to a cage structure (Figure 18b). [ 99 ] Alkaline metal doping of boron clusters has also been extensively studied by CALYPSO code, which suggests that alkaline metal doping can greatly improve the stability of boron clusters (Figure 18c).…”
Section: Introduction To Existing Cluster Search Methodsmentioning
confidence: 99%
“…36,37 In the CALYPSO based cluster structure prediction study of Tian's group, we found that they mentioned a number of interesting phenomena for metal-doped boron clusters with Li 2 B 24 tubular structures, MgB 18 drum-like tubular clusters, BeB 38,39 The properties and geometry of atomic clusters are sizedependent and highly sensitive to the nature of the dopant. [40][41][42] Yang's group searched for the structure of the Cs 2 B n (n = 1-12) clusters using unbiased crystal structure analysis and determined the global minimum. It was found that the ground state structures of the clusters have four geometries: arch-bridge, planar, shielded shape, and bipyramidal.…”
Section: Introductionmentioning
confidence: 99%
“…The properties and geometry of atomic clusters are size-dependent and highly sensitive to the nature of the dopant. 40–42 Yang's group searched for the structure of the Cs 2 B n ( n = 1–12) clusters using unbiased crystal structure analysis and determined the global minimum. It was found that the ground state structures of the clusters have four geometries: arch-bridge, planar, shielded shape, and bipyramidal.…”
Section: Introductionmentioning
confidence: 99%
“…This method is capable of providing not only Lewis's bonding elements (1c-2e lone pairs and 2c-2e "classical" bonds) but also a non-classic multi-center representation of delocalized bonds (nc-2e bonds, where n � 3), which allows to introduce the concepts of aromaticity naturally. AdNDP is effectively used to decipher the chemical bonding pattern of molecules, [24,25] solid materials, [28,29] and clusters, which is the most essential for the current work; more specifically, it was applied for describing and interpreting structure properties of Boron clusters, [30][31][32][33] Aluminum clusters, [34][35] Tin clusters, [36][37] Germanium [38][39][40] and many others. [41][42][43][44][45][46][47] This makes the approach adequate for bonding analysis of bismuth polycation clusters.…”
Section: Introductionmentioning
confidence: 99%